Implementing ecological intensification in fish farming: definition and principles from contrasting experiences - Joël Aubin; Myriam Callier; Hélène Rey‐Valette; Syndhia Mathé; Aurélie Wilfart; Marc Legendre; Jacques Slembrouck; Domenico Caruso; Eduardo Chia; Gérard Masson; Jean Paul Blancheton; Ediwarman; et al. (Reviews in Aquaculture, 2019)
Ecological intensification is a new concept in agriculture that addresses the double challenge of maintaining a level of production sufficient to support needs of human populations and respecting the environment in order to conserve the natural world and human quality of life. This article adapts this concept to fish farming using agroecological principles and the ecosystem services framework. The method was developed from the study of published literature and applications at four study sites chosen for their differences in production intensity: polyculture ponds in France, integrated pig and pond polyculture in Brazil, the culture of striped catfish in Indonesia and a recirculating salmon aquaculture system in France. The study of stakeholders’ perceptions of ecosystem services combined with environmental assessment through Life Cycle Assessment and Emergy accounting allowed development of an assessment tool that was used as a basis for co‐building evolution scenarios. From this experience, ecological intensification of aquaculture was defined as the use of ecological processes and functions to increase productivity, strengthen ecosystem services and decrease disservices. It is based on aquaecosystem and biodiversity management and the use of local and traditional knowledge. Expected consequences for farming systems consist of greater autonomy, efficiency and better integration into their surrounding territories. Ecological intensification requires territorial governance and helps improve it from a sustainable development perspective.